2018
DOI: 10.1155/2018/6196289
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Anethole and the Essential Oils of Lemongrass and Sweet Marigold to the Parasitic Mite Varroa destructor and Their Selectivity for Honey Bee (Apis mellifera) Workers and Larvae

Abstract: This study examined the toxicity of anethole and that of the essential oils of lemongrass (Cymbopogon citratus) and sweet marigold (Tagetes lucida) to the mite Varroa destructor and to honey bee workers and larvae. Anethole was the most toxic compound to V. destructor (LC50: 304.9 μg/ml), whereas Tagetes oil was the least toxic (LC50: 1256.27 μg/ml). The most and least toxic compounds to worker bees were anethole and Tagetes oil with LD50s of 35942 and 85381 μg/ml, respectively. For larvae, Tagetes oil was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Therefore, it is of utmost importance to develop effective supply systems, as well as frequent and optimal dosages to determine the optimum moment of application 53 and to use an integrated phytotherapeutic management against varroasis, which alternates EOs such as garlic (Allium sativum) 54 , oregano (Origanum vulgare) 51 , laurel (Laurus nobilis) 55 , neem (Azadirachta indica), lemon grass (Cymbopogon spp.) 56 , among others, whose results are efficient.…”
Section: Developmentmentioning
confidence: 99%
“…Therefore, it is of utmost importance to develop effective supply systems, as well as frequent and optimal dosages to determine the optimum moment of application 53 and to use an integrated phytotherapeutic management against varroasis, which alternates EOs such as garlic (Allium sativum) 54 , oregano (Origanum vulgare) 51 , laurel (Laurus nobilis) 55 , neem (Azadirachta indica), lemon grass (Cymbopogon spp.) 56 , among others, whose results are efficient.…”
Section: Developmentmentioning
confidence: 99%
“…Nevertheless, citral was successful in controlling tracheal mites under hive conditions, reducing their population by 66.8%. In another study, Sabahi et al (2018) studied the toxicity of several compounds, including the essential oil of lemongrass (containing mainly citral), on varroa mites and honey bees, finding that lemongrass with a LC 50 of 470 μl/ml was one of the most effective compounds against V. destructor mites. Moreover, the LD 50 value of this essential oil for adult bees was >50,000 μl/ml, which was >100 times less toxic for adult bees than for mites.…”
Section: Discussionmentioning
confidence: 99%
“…Biocontrol of V. destructor has been attempted with poor results (Meikle et al, 2012; Sinia & Guzman‐Novoa, 2018), but plant‐derived organic compounds seem to be more promising. The testing and use of essential oils and extracts from aromatic plants has increased, since some seem to be efficacious against V. destructor , and also because these compounds are considered low‐risk pesticides by organic producers and consumers concerned about the environment (Blenau et al, 2012; Damiani et al, 2011; Iglesias et al, 2021; Koul et al, 2008; Sabahi et al, 2017; Sabahi et al, 2018; Sabahi et al, 2020). However, so far, only thymol alone or combined with other essential oils is available in commercial formulations of varroacides.…”
Section: Introductionmentioning
confidence: 99%
“…aegypti larvae (LC 50 : Garlic = 0.006 ppm and anise = 0.020 ppm at after 24-h exposure). Our results were compared with the criteria of Cheng et al [20] which describes that if the LC 50 <50 ml/L (or ppm), means that it has a highly efficacy against the larvae of mosquitoes. This result was consistent with the previous biological research, which found that garlic and anise essential oils are toxic to mosquito species including Culex restuans (LC 50 : garlic = 2.7 ppm) and Cx.…”
Section: Discussionmentioning
confidence: 99%